Metacognitive Education in Improving Student's Interpersonal Intelligence - Ubaidillah, Ubaidillah; Muntoha, Tohir; Khomsinnudin, Khomsinnudin; Khasanudin, M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2021)
Intrapersonal intelligence is necessary for everyone to advance more competent abilities and personalities. As a result, initiatives to develop intelligence must be addressed, one of which is metacognitive education. Metacognition is seen to have a tight relationship with intrapersonal intelligence. Its concepts and theories have a number of similarities. This research was a qualitative study using a library research method which was used to acquire research data by reading, listening to, and interpreting both written and recorded books, notes, reports, and journals. The findings of this study suggest that students' intrapersonal intelligence may potentially be increased by metacognitive education using a set of acceptable techniques developed by education specialists.